Electrostimulation triggers an increase in cross-niche microbial associations toward enhancing organic nitrogen wastewater treatment. (1st April 2023) - Shi, Ke; Liang, Bin; Feng, Kai; Ning, Daliang; Cornell, Carolyn R.; Zhang, Yanqing; Xu, Wenbin; Zhou, Min; Deng, Ye; Jiang, Jiandong; Liu, Tiejun; Wang, Aijie; et al.
Abstract: As an efficient wastewater pretreatment biotechnology, electrostimulated hydrolysis acidification (eHA) has been used to accelerate the removal of refractory pollutants, which is closely related to the effects of electrostimulation on microbial interspecies associations. However, the ecological processes underpinning such linkages remain unresolved, especially for the microbial communities derived from different niches, such as the electrode surface and plankton. Herein, the principles of cross-niche microbial associations and community assembly were investigated using molecular ecological network and phylogenetic bin-based null model analysis (iCAMP) based on 16S rRNA gene sequences. The electrostimulated planktonic sludge and electrode biofilm displayed significantly ( P  < 0.05) 1.67 and 1.53 times higher organic nitrogen pollutant (azo dye Alizarin Yellow R) degradation efficiency than non-electrostimulation group, and the corresponding microbial community composition and structure were significantly ( P  < 0.05) changed. Electroactive bacteria and functional degraders were enriched in the electrode biofilm and planktonic sludge, respectively. Notably, electrostimulation strengthened the synergistic microbial associations (1.8 times more links) between sludge and biofilm members. Additionally, both electrostimulation and cross-niche microbial associations induced greater importance of deterministic assembly. Overall, this study highlights the specificity of cross-electrode surface microbial associations and ecological processes with electrostimulation and advances our understanding of the manipulation of sludge microbiomes in engineered wastewater treatment systems. Graphical abstract: Image 1 Highlights: The electrostimulated sludge had obviously higher pollutant degradation efficiency. Sludge community at different niche markedly shifted upon electrostimulation. More microbial associations of cross-niche evolved upon electrostimulation. Electrostimulation/cross-niche biotic factors contributed to deterministic assembly.